Industrialization and the Big Push: Theory and Evidence from South Korea - Choi, Jaedo; Shim, Younghun (The Review of Economics and Statistics, 2026)
We study how temporary subsidies for adoption of modern foreign technology drove South Korea’s industrialization in the 1970s. Leveraging unique historical data, we provide causal evidence consistent with coordination failures: adoption improved adopters’ performance and generated local spillovers, with firms more likely to adopt when other local firmshad already adopted.We incorporate these findings into a quantitative model, where the potential for multiple steady states depends on parameters mapped to the causal estimates. In our calibrated model, South Korea’s temporary subsidies shifted its economy to a more industrialized steady state, increasing heavy manufacturing’s GDP share by 27% and export intensity by 39%. Larger market access and lower idiosyncratic distortions amplified the effects of these subsidies, as the gains from adoption increase with firm scale.